STUDI KERENTANAN TSUNAMI DI KECAMATAN NGAMBUR DAN BENGKUNAT, PESISIR BARAT LAMPUNG MENGGUNAKAN COMCOT - Fauzi, Muhammad Aldhiansyah Rifqi; Chairiyah, Hani Fathul; Ahmad, Ayu Libiaty; Tarigan, Trika Agnestasia Br (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
Bengkunat and Ngambur districts are located in West Pesisir Regency, Lampung Province, these are located on the southern coast of the island of Sumatra. Tsunami disasters can occur at any time if there is a generator such as a seafloor earthquake and cannot be predicted when it will occur and will be destructive or not. This research is modeling wave propagation using COMCOT program to determine tsunami wave propagation, run-up, arrival time and inundation. The magnitude scenarios used are 6.5, 7.5 and 8.5. Tsunami waves in Bengkunat and Ngambur districts showed destructive tsunami potential in each scenario. Wave height, wave inundation area and wave arrival time vary due to differences in magnitude as well as the geographical conditions of the coast and its bathymetry. The higher the magnitude, the higher the wave height and the faster the arrival time. Pagar Bukit, Suka Negara, Muara Tembulih and Sumber Agung are villages with significant damage because the wave height is above 8 m with arrival times ranging from 29-34 minutes. While Padang Dalam, Gedung Cahaya Kuningan and Parda Suka, the wave height is between 2-6 meters with a time ranging from 35-39 minutes, Inundation at magnitude 6.5 only hits the coastal area only as far as 220 meters, but at magnitude 7.5 inundation reaches about 2.4 kilometers while at magnitude 8.5 inundation reaches 3.4 kilometers.